Programa educativo “Dale pecho, Dale vida” y nivel de conocimiento de la Lactancia Materna Exclusiva - Perez Aguilar, Clementina Victoria (2022)
This thesis is a quantitative pre-experimental study that examined the effectiveness of the educational program "Dale pecho, dale vida" on the knowledge about exclusive breastfeeding of 40 primiparous mothers with children under 6 months of age, who attended the Hospital de Especialidades Básicas La Noria. Two instruments were used: a questionnaire to determine the participants' knowledge of exclusive breastfeeding and the educational program "Dale pecho, Dale vida". IBM SPSS 25.0 statistical software was used. Before the application of the educational program, 55 percent of the mothers had low knowledge, followed by 42.5 percent with medium knowledge and finally 2.5 percent with high knowledge. After the application of the educational program, it was found that 75 percent of the mothers had a high level of knowledge and 25 percent had a medium level of knowledge. For the statistical analysis, the Wilcoxon nonparametric test was used, concluding that the educational program was effective in increasing the level of knowledge about exclusive breastfeeding in primiparous mothers